Analysing the context and characteristics of legal abortion and comprehensive post-abortion care among adolescents aged 10–14 in a network of sentinel centres in Latin America: a retrospective cross-sectional study, 2016–2020 - Caitlin R. Williams; M. Valeria Bahamondes; Rodolfo Gómez Ponce de León; Helymar da Costa Machado; Luis Bahamondes; Sonja Caffe; Suzanne Jacob Serruya (Sexual and Reproductive Health Matters, 2023)
Pregnancy-related complications are a substantial source of morbidity and mortality among adolescents in low- and middle-income countries. While the youngest adolescents (those aged 10–14) are considered to be at particularly high risk of adverse outcomes, there is little empirical data available on their sexual and reproductive health. Using a unique dataset of clinical records drawn from a regional network of sentinel centres providing legal abortion and comprehensive post-abortion care in 12 Latin American and Caribbean countries, we described the population of adolescents aged 10–14 seeking legal abortion and post-abortion care and calculated institutional rates of complications, using older adolescents (aged 15–19) and young adults (aged 20–24) as comparator groups. We also assessed the quality of care provided as compared to WHO recommendations. Nearly 17% (89 out of 533) of young adolescents sought care when they were already at 15 or more weeks’ gestation. Young adolescents were at higher risk of pre-procedure and intra-operative complications than older adolescents and young adults, though the trend is less clear for the most severe complications. In general, the quality of care provided by centres in the network was aligned with WHO recommendations for safe abortion and comprehensive post-abortion care. Taken together, these findings provide insight into the challenges facing the global health community in assuring the sexual and reproductive health and rights of the youngest adolescents, and outline avenues for future research, advocacy, and evidence-based policymaking.